Mechanochemical synthesis and thermal decomposition of zinc borohydride - Jeon, Eun; Cho, YoungWhan (ELSEVIER SCIENCE SA, 2006)
Zinc borohydride Zn(BH4)(2) (8.5 wt% theoretical hydrogen storage capacity) has been synthesized by mechanochemical reaction between NaBH4 and ZnCl2 and its structure was analyzed by XRD and FT-IR. The thermal stability of Zn(BH4)(2) in the presence of inert by-product NaCl was studied by TG/MS and DSC under flowing argon. It melts at about 85 degrees C and starts to decompose almost at the same time producing diborane B2H6 and hydrogen gases between 85 and 140 degrees C. The decomposition reaction is endothermic and the remaining solid product after decomposition is Zn with a trace of B. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: HYDROGEN STORAGE PROPERTIES; METAL; HYDRIDES; LIH